Disposisi Matematis Dan Kemandirian Belajar Mahasiswa Pada Perkuliahan Daring Berbantuan Google Classroom Masa Covid-19 - Friantini, Rizki Nurhana; Winata, Rahmat (Pendidikan Matematika Universitas PGRI Yogyakarta, 2020)
This study aims to analyze the mathematical disposition and self-regulated learning of online lectures with the help of Google Classroom. This type of research is descriptive quantitative. This study's subjects were 34 students of the first semester of the Mathematics Education Study Program consisting of 11 male students and 23 female students determined by the saturated sampling method. From the research results, it can be concluded that students' mathematical disposition through learning assisted by Google Classroom has high criteria. The mathematical disposition of male and female students through learning assisted by Google Classroom has high criteria. Still, the level of mathematical disposition of male students is slightly higher than female students. Meanwhile, student self-regulated learning with the help of Google Classroom obtains very high criteria. For male and female students, both have very high learning independence criteria in carrying out learning with the help of Google Classroom.Keywords: Mathematical Disposition, Self-regulated learning, Google Classroom, Online Lectures, Gender